THE IMPACT OF CAPITAL STRENGTHENING IN CULTURE ON THE WELFARE OF INDONESIAN UMKM COMMUNITIES IN GORONTALO - Ariawan, Ariawan; Widjaja, Warkianto; Judijanto, Loso; Budiman, Riadi; Bakri, Asri Ady (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2025)
This study analyzed the influence of community participation and cultural capital on micro, small, and medium enterprises. The growth of micro-businesses in the community is still minimal, so it is urgent and valuable to study the expansion of the micro-business sector in Gorontalo. The research method used is quantitative, with a sample of 170 micro, small, and medium enterprises in Gorontalo and a random cluster sampling selection. Data collection techniques using questionnaires. Descriptive and regression analysis techniques and SPSS Version 29.0 analysis. The results found that the success and creativity of micro businesses are significantly influenced by cultural capital and community participation. It was found that cultural capital and community participation in Gorontalo are essential for increasing micro businesses. In conclusion, small and medium businesses can grow and contribute significantly to the economy by strengthening cultural and community capital. The study implies that it encourages the government to create cultural capital and community participation in the regional economy. JEL: L26, O15, O35.